Mn(iv) and Mn(v)-radical species supported by the redox non-innocent bis(2-amino-3, 5-di-tert-butylphenyl)amine pincer ligand. Issue 18 (17th February 2017) - Leconte, Nicolas; Moutet, Jules; Herasymchuk, Khrystyna; Clarke, Ryan M.; Philouze, Christian; Luneau, Dominique; Storr, Tim; Thomas, Fabrice
Abstract : The electron-rich pincer ligand1 has been synthesized and chelated to manganese, affording2 in high yield. Complex2 comprises two iminosemiquinone radicals coordinated to a Mn(iv ) ion. Its two electron oxidation produces2 2+, which is a stable Mn(v )-iminosemiquinone radical complex. Abstract : The electron-rich pincer ligand1 has been synthesized and chelated to manganese. The octahedral Mn(iv ) bis(diiminosemiquinonate) and Mn(v ) (diiminobenzoquinone) (diiminosemiquinonate) radicals were structurally characterized.